Jendela Logika dalam Berfikir: Deduksi dan Induksi sebagai Dasar Penalaran Ilmiah - Mustofa, Imron (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2016)
Logic has a very important role in the development of knowledge and the study of certain knowledge. As a science, it is the basis that determines thinking to be straight, precise and healthy. Because the function of logic is to investigate, formulate and apply the laws that are kept. Logic is a science that provides principles that must be followed in order to think validly according to the applicable rules. This is because, Scientific reasoning requires integrated proof of truth. Between rational and factual or deductive and inductive truths, both of which use hypotheses as a bridge. both of which use hypotheses as a bridge bridge. Both deductive and inductive are not without flaws, hence the need for further identification, in order to arrive at a scientific reasoning method that agrees with integrated proof, between rational and factual truth. rational and factual truth.